Italy : Quantifying the Benefits of a Comprehensive Reform Package - Andrle, Michal (IMF Working Papers; Working Paper ;, 2018)
This paper seeks to quantify the net benefits of a comprehensive reform package aimed at addressing Italy's inter-related challenges. Specifically, it simulates the growth and competitiveness effects of a package of fiscal, financial, wage bargaining, and other structural reforms. Credible implementation of such a package yields substantial mediumterm dividends at negligible near-term growth costs. Real GDP growth is estimated to be substantially higher over the medium term, while the real effective exchange rate depreciates notably.